Influence of spiking activity on cortical local field potentials. (25th September 2013) - Waldert, Stephan; Lemon, Roger N.; Kraskov, Alexander
Key points: The intra‐cortical local field potential (LFP) reflects a variety of electrophysiological processes and is a fundamental signal used to enhance knowledge about neuroscience. For most investigations, spike‐free LFPs are mandatory for valid conclusions, but spikes can contaminate LFPs and falsify findings despite low‐pass filtering or other attempts to remove spiking activity from LFPs. The extent of this fundamental problem remains unclear. Using spikes recorded in the awake monkey, we revealed how spike amplitude, spike duration, firing rate and noise statistic influence the extent to which spikes contaminate LFPs. Contamination varies with these parameters and can affect LFPs down to around 10 Hz; below this it is theoretically possible but unlikely. LFP frequencies up to the (high‐) gamma band can remain unaffected, but signals above must always be carefully analysed. We propose a method to reveal modulations in spectrograms, which also allows the detection of spike contamination, and provide a systematic guide to assess spike contamination of intra‐cortical LFPs. Abstract The intra‐cortical local field potential (LFP) reflects a variety of electrophysiological processes including synaptic inputs to neurons and their spiking activity. It is still a common assumption that removing high frequencies, often above 300 Hz, is sufficient to exclude spiking activity from LFP activity prior to analysis. Conclusions based on such supposedly spike‐free LFPs can result in false interpretations of neurophysiological processes and erroneous correlations between LFPs and behaviour or spiking activity. Such findings might simply arise from spike contamination rather than from genuine changes in synaptic input activity. Although the subject of recent studies, the extent of LFP contamination by spikes is unclear, and the fundamental problem remains. Using spikes recorded in the motor cortex of the awake monkey, we investigated how different factors, including spike amplitude, duration and firing rate, together with the noise statistic, can determine the extent to which spikes contaminate intra‐cortical LFPs. We demonstrate that such contamination is realistic for LFPs with a frequency down to ∼10 Hz. For LFP activity below ∼10 Hz, such as movement‐related potential, contamination is theoretically possible but unlikely in real situations. Importantly, LFP frequencies up to the (high‐) gamma band can remain unaffected. This study shows that spike–LFP crosstalk in intra‐cortical recordings should be assessed for each individual dataset to ensure that conclusions based on LFP analysis are valid. To this end, we introduce a method to detect and to visualise spike contamination, and provide a systematic guide to assess spike contamination of intra‐cortical LFPs.